Literacy Program to Increase Reading interest in Third-Grade Elementary School Students - Reni Lolotandung; Trivena Trivena (Universitas Muhammadiyah Enrekang, 2022)
The aim of this study was to determine the role of literacy in increasing reading interest in 3rd grade elementary school students. The research method used in this research is qualitative research. The informants of this study were the principal, the homeroom teacher, and 3rd grade elementary school students. Data collection techniques through observation, interviews, and documentation The collected data is then processed through the phases of data reduction, data presentation, and data verification. The results showed that the literacy program was good at increasing reading interest in 3rd grade elementary school students. The role of literacy is very important in increasing students' interest in reading in Grade III. The literacy program is phased, with an emphasis on the habituation phase (15-minute reading), the development phase (answers to enriching books), and the learning phase (linking literacy in all subjects). From this, it can be concluded that the better the implementation of the school literacy movement supports the increase in the students' interest in reading. Therefore, the implementation of literacy in primary schools needs to be improved, not only for reading skills but also for other literacy.